Pengaruh Penerapan Reward dan Punishment Terhadap Hasil Belajar Pendidikan Agama Islam Dan Budi Pekerti Peserta Didik di SMP Muhammadiyah Limbung Kecamatan Bajeng Kabupaten Gowa. - Rofiqah Al Munawwarah (Prodi Manajemen Pendidikan Islam Institut Parahikma Indonesia, 2018)
This research discussed about The Effect of the Application of Reward and Punishment on the Learning Results of Islamic Religious Education and the Character of Students at SMP Muhammadiyah Limbung District Bajeng, Gowa Regency. The type of this research that was used was quantitative research, expost facto. Expost facto is the research to examine the events that have occured, the data in the form were numbers and using statistical analysis with simple regression. The sample of this research were VIIC class of 21 students with sampling technique of Proportionate Stratifide Random Sampling which is sampling technique with focusing on the level in population. The approach that was used is correlational approach. The instruments were questionnaires and documentation records. Data analysis techniques that were used descriptive statistics and inferential statistics. Based on descriptive statistical analysis, the average score of the application of reward and punishment in learning fiqh was 144 at interval 39-148, this result was in high category. The average score of student learning outcomes was 79 at the interval 78-81, this result was in the high category. While the results of analysis on statistical tests? 0 = 5.80 ???? = 2.09? 0> ????? (5.80> 2.09) so that ?? rejected? 1 accepted. Thus it can be concluded that the application of reward and punishment in learning fiqh affects of the students learning results of fiqh in SMP Muhammadiyah Limbung District Bajeng, Gowa Regency. The implications in this research were the application of Reward and Punishment can be applied in the learning process in order to achieve the learning objectives and improve student learning results, as well as to contribute thoughts to various parties, either for students, teachers and or the other educators.